The Role of Progranulin (PGRN) in the Pathogenesis of Glioblastoma Multiforme - Łukasz A. Poniatowski; Michał Woźnica; Piotr Wojdasiewicz; Aneta Mela-Kalicka; Katarzyna Romanowska-Próchnicka; Daryush Purrahman; Grzegorz Żurek; Maciej Krawczyk; Najmeh Nameh Goshay Fard; Marzena Furtak-Niczyporuk; Janusz Jaroszyński; Mohammad-Reza Mahmoudian-Sani; et al. (Cells, 2024)
Glioblastoma multiforme (GBM) represents the most common and aggressive malignant form of brain tumour in adults and is characterized by an extremely poor prognosis with dismal survival rates. Currently, expanding concepts concerning the pathophysiology of GBM are inextricably linked with neuroinflammatory phenomena. On account of this fact, the identification of novel pathomechanisms targeting neuroinflammation seems to be crucial in terms of yielding successful individual therapeutic strategies. In recent years, the pleiotropic growth factor progranulin (PGRN) has attracted significant attention in the neuroscience and oncological community regarding its neuroimmunomodulatory and oncogenic functions. This review of the literature summarizes and updates contemporary knowledge about PGRN, its associated receptors and signalling pathway involvement in GBM pathogenesis, indicating possible cellular and molecular mechanisms with potential diagnostic, prognostic and therapeutic targets in order to yield successful individual therapeutic strategies. After a review of the literature, we found that there are possible PGRN-targeted therapeutic approaches for implementation in GBM treatment algorithms both in preclinical and future clinical studies. Furthermore, PGRN-targeted therapies exerted their highest efficacy in combination with other established chemotherapeutic agents, such as temozolomide. The results of the analysis suggested that the possible implementation of routine determinations of PGRN and its associated receptors in tumour tissue and biofluids could serve as a diagnostic and prognostic biomarker of GBM. Furthermore, promising preclinical applications of PGRN-related findings should be investigated in clinical studies in order to create new diagnostic and therapeutic algorithms for GBM treatment.